The photographer's guide to Adobe Lightroom learn industry -standard best practices and techniques to get the best out of the latest version of Lightroom classic - Lewandowski, Marcin (PACKT PUBLISHING LIMITED, 2022)
Get better at Adobe Lightroom to streamline post-production and focus on creativity Key Features Manage, edit, and post-produce photographs in one place with the help of this full-color guide Adopt a non-destructive approach to working with seemingly infinite copies of photographs with different looks Increase productivity and make your creative process easier with Lightroom's functionality and additional tools Book Description It takes talent to be a great photographer, but in the digital era, it also takes a level of technical proficiency. Adobe Photoshop Lightroom Classic was designed as a one-stop solution for photographers to perfect their final products on a desktop-focused workflow, which includes local storage of your photos in files and folders on your computer. Knowing how to efficiently navigate through Lightroom means that you'll be able to concentrate on being creative instead of wondering "what does this button do". Complete with step-by-step explanations of essential concepts and practical examples, you will begin with importing photographs into Lightroom. You'll focus on how to sort through, sequence, develop, and export ready files in various formats, or even design a book and create gallery-ready prints. Next, you will learn how to make informed decisions within Lightroom and how to approach your work depending on the set of photographs you are working on. This guide also illustrates real-life usage and workflow examples that are not just for aspiring professionals, but also for artists and amateurs who are still getting to grips with the technical side of photography. By the end of this book, you'll be confident in importing, editing, sorting, developing, and delivering your photos like a professional. What you will learn Import photographs from different sources Understand how to create and refine edits Use and manage catalogs, folders, and collections Develop photographs using all available tools Prepare files for print and online viewing Create slideshows and book layouts Who this book is for This is a book for photographers who've used Lightroom in the past but need a structured approach to start making the most of its advanced features. If you're a beginner who's willing to invest a bit of time in understanding Lightroom's basic functionality, you can use it just as well - but you may need to look at a few external sources along the way. Essentially, this photography book is for anyone who wants to become proficient enough in Lightroom to make better decisions and focus on creativity instead of the software.